ONE YEAR CLINICAL EXPERIENCE OF CBD STONES IN POST OPERATIVE CHOLECYSTECTOMY CASES WITH REMNANT GALL BLADDER: A CASE SERIES - Dr. M.Nupur; Dr. Siddhartha Sankar Konwar; Dr. Geevar Alex; Dr. Dibyajit Chakravarty; Dr. Prosperwell War; Dr. Lipika Sarma (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
.